The scandalous adventures of the sister of the bride [large type] - Alexander, Victoria (Center Point Large Print, 2014)
"Lady Delilah Hargate and Mr. Samuel Russell spent one unforgettable night together in New York City. Now attending the wedding of her sister and his friend at Millworth Manor, they pretend they have never met before. But delightful grounds, lavish drawing rooms, and secluded corners provide the chance to discover that one night was only the beginning"--